Marketing social e infeção por VIH/SIDA nas pessoas com mais de 50 anos - Ribeiro, Ana Isabel de Almeida (2012)
The Social Marketing aims to change behaviors, encourage social awareness in each individual, forcing the adoption of new habits that are important for the person and society. Their growth becomes larger and even more significant, The higher the concern with social problems, such as infection by the HIV / AIDS. This is one of the issues that most concern today's society, not only by the proportions that has taken over time, with increased morbidity, but also by all the economic and social costs generated by it. Recent studies show an exponential increase of this syndrome in the population over 50 years, and social marketing could be used as a strategy to resolve this. The current research aimed to discuss and obtain information on the relationship of the two components addressed, Social Marketing and HIV infection / AIDS, in common with citizens over 50 years, having come to the conclusion that risk behaviors are higher the expected, and the health education, disease awareness and changing behaviors and attitudes are the most effective tools for monitoring, managing them easily through social marketing.